Cooperation, Competition and Conflict: A Historical Analysis of the Religious and Socio-Political Relations of Pentecostal Churches in Kaduna Metropolis, 1970-2020 - Ashafa, Abdullahi Musa; Wuam, Terhemba; Aloko, Sunday Moses Adebayo (NIU Journal of Humanities, 2025)
The focus of this article is the religious pluralism of the Kaduna Metropolis, and its socio-political implications on inter- and –intra –faith relations in a rapidly changing urban context. It examines the relationship between Pentecostal churches, other Christian denominations, non-Christians, and the institution of the state between 1970 and 2020. Against this background, it investigates the factors that have necessitated Christian collaboration such as the shared objectives of proselytization, common socio-political concerns, and joint initiatives such as such as crusades and community development projects in the metropolis. It also analyses the elements that have fuelled inter and intra-religious tensions, especially the pursuit of followership, as well as the regulatory roles of the Kaduna State Government which has been a subject of debate. On the strength of largely primary sources, research findings reveal that Pentecostalism's growth in Kaduna Metropolis has engendered complex relationships with religious and secular institutions. Initial interdenominational tensions within Christianity evolved into cooperation and cross-denominational influence. Simultaneously, Pentecostal churches navigated interreligious (Christian-Muslim) dynamics and contributed to both peacebuilding and conflict. The article concludes that their relationship with the Kaduna State Government is also marked by cooperation and tension, fueled by concerns regarding religious freedom and perceived marginalization, which underscores the need for interfaith dialogue and collaborative governance. Keywords: Cooperation, Competition, Conflict, Pentecostalism, Relations